KONFLIK AGRARIA DALAM PENGADAAN TANAH UNTUK KEPENTINGAN UMUM â€œSTUDI KASUS DESA WADAS PURWOREJOâ€ - Sejarot, Diyan; Achmad Hariri (Faculty of Law, University of Muhammadiyaha Surabaya, 2023)
The designation of Wadas village as an andesite rock mining area to support the construction of the Bener Dam national strategic project in Purworejo, Central Java, is the reason for the emergence of agrarian conflicts between the community and the initiators of the project. This study aims to find out how the Land Acquisition Arrangements for Development for the Public Interest and whether andesite rock mining in Wadas Village, Bener, Purworejo Regency, Central Java does not require a rock mining permit (SIPB) and how certain Rock Mining Arrangements for certain purposes are based on the prevailing laws and regulations in Indonesia. The research method used is a normative research method with a Statutory approach and a Conceptual approach. The results of this study show that Land Acquisition for Development for The Public Interest is regulated in Law Number 2 of 2012, andesite Rock Mining in wadas village does not include land acquisition for the public interest so that it requires a rock mining permit (SIPB) so that the rock mining plan can be implemented. The implementation of Rock Mining is regulated in Law Number 3 of 2020 and its implementing regulations. Mining activities or businesses that are currently occurring have violated Law Number 32 of 2009, Law Number 3 of 2020, Government Regulation of the Republic of Indonesia of 2021, and Regulation of the Minister of Energy and Mineral Resources Number 5 of 2021.Keywords: Agrarian Conflict, Land Acquisition, Rock Mining, Wadas